Diskursus tentang Kebolehan Jamak Salat dalam Hadis Perspektif Sunni dan Syiah - Roihana Purnamasari, Umi Nashiroh; Said, Imam Ghazali (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
This article discusses the comparison of the permissibility of combining prayers according to the hadith from the perspective of Sunni and Shia, two major schools of thought in Islam. This study aims to discuss the hadith basis that underpins the practice of combining prayers, both in emergency situations and outside of emergency situations, according to the interpretations of both sects.The method used is qualitative analysis through literature review, such as hadith books, books containing the views of prominent scholars from each school of thought, articles and related scientific works. The research results show that the Sunni school generally permits combining prayers under certain conditions such as travel, rain, or emergencies, based on hadiths narratedÄ by the Prophet's companions. Meanwhile, the Shia school of thought is more flexible in allowing combining prayers, not limited to emergency conditions, based on the traditions of the Infallible Imams. This comprehensive research reveals that the differences in perspective are rooted in the methodological approaches to hadis interpretation and the mechanisms of authority legitimation in legal determination.